2021
DOI: 10.3389/fpsyg.2020.581086
|View full text |Cite
|
Sign up to set email alerts
|

Being Mindful at University: A Pilot Evaluation of the Feasibility of an Online Mindfulness-Based Mental Health Support Program for Students

Abstract: University study can be a life period of heightened psychological distress for many students. The development of new preventive and intervention programs to support well-being in university students is a fundamental challenge for mental health professionals. We designed an 8-week online mindfulness-based program (eMBP) combining a face-to-face approach, text, audio, video components, and support psychotherapy principles with a unique intensive reminder system using the Facebook Messenger and Slack applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 87 publications
2
10
0
5
Order By: Relevance
“…The current study found that the RMMt-P had a negative correlation with anger, whereas the FMI-P scale did not. Consistent with the findings of the current study, Světlák et al (2021) measured mindfulness in students using the FFMQ as a broadband scale and found that mindfulness reduced perceived stress, the frequency and severity of negative effects, and increased self-compassion ( Světlák et al, 2021 ), all of which can reduce people’s anger.…”
Section: Discussionsupporting
confidence: 86%
“…The current study found that the RMMt-P had a negative correlation with anger, whereas the FMI-P scale did not. Consistent with the findings of the current study, Světlák et al (2021) measured mindfulness in students using the FFMQ as a broadband scale and found that mindfulness reduced perceived stress, the frequency and severity of negative effects, and increased self-compassion ( Světlák et al, 2021 ), all of which can reduce people’s anger.…”
Section: Discussionsupporting
confidence: 86%
“…As college students are very susceptible to high health-risk behaviours, a recent work [ 144 ] demonstrated that mindfulness-based intervention has valuable effects in both improving mindfulness and reducing many such behaviours. Similar results were reported by [ 145 ], who evaluated an online mindfulness-based mental health support programme for students, evaluating its effects on mindful experiencing, perceived stress, emotion regulation strategies, self-compassion, negative affect, and quality of life. Application of mindfulness programmes resulted in a reduction of perceived stress, a decreased frequency and intensity of negative affect experiences, and an increase in being mindful in life.…”
Section: Learning Stimulation Based On Neuroscientific Findingssupporting
confidence: 83%
“…The evidence supporting MBIs to achieve a range of positive psychological and health outcomes demonstrates that mindfulness training is a promising intervention to utilise for the prevention of student mental ill health, and promotion of positive mental wellbeing (Světlák et al, 2021). Additionally, the ease of transferring it to an online environment with low cost, relatively minimal time and potentially high reach -makes a MBI an ideal online wellbeing resource allowing universities to provide more inclusive, integrated and accessible resources -including for on-campus and fully online students.…”
Section: Introductionmentioning
confidence: 99%